Traditional Villages and Smart cities: Planning Rural Greece’s Revival through Potential Erasmus+ Training Courses - Pelagidou, Maria Argyro (HAPSc Policy Briefs Series, 2022)
This paper discusses the potential of Greece to accommodate more training courses that could be funded by Erasmus+. Its limitation is that it suggests potential training courses mostly on the topics of preserving local culture and developing smart city technologies. Scarcity in Erasmus+ training courses and hosting cities highlights the need for a more creative approach to the subject. Traditional villages and smart-cities are located in the center of the creation of new training courses. This, in turn, would create job opportunities and help transmit knowledge from the hosts of the courses to the incoming trainees and vice-versa. A variety of training courses is proposed to take place in rural areas and attract specific categories of trainees.